Reformasi Birokrasi Dalam Kualitas Pelayanan Publik: Suatu Tinjauan Literatur - Zahwa Alia Putri; Silvia Silvia; Siti Nur Aisyah; Viola Nofrilia; Jumiati Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effectiveness of bureaucratic reform in improving the quality of public services in Indonesia through a literature review approach. This study examines selected scientific articles from the last ten years that discuss various aspects of bureaucratic reform, including service efficiency, transparency, accountability, citizen satisfaction, and the role of digitalization.The findings reveal that bureaucratic reform has positively impacted service acceleration, public trust enhancement, and the adoption of information technologies such as e-government. Nevertheless, implementation still faces challenges such as bureaucratic resistance, limited funding, and lack of inter-agency coordination. This study recommends strengthening leadership, enhancing bureaucratic human resources, increasing public participation, and fostering cross-sector policy synergy to support sustainable bureaucratic reform.